Differentiating Between Conceptual and Theory Articles: Focus, Goals, and Approaches. (March 2022) - Rocco, Tonette S.; Plakhotnik, Maria S.; Silberman, Dave
The purpose of this article is to promote conceptual and theoretical scholarship in human resource development by providing insights and guidance on differences between conceptual and theory articles and when and how to create such scholarship. First, we discuss the role of Human Resource Development Review and conceptual and theory articles in assisting human resource development in developing into a profession and expanding the field. Then, we determine that conceptual and theory articles are non-empirical works that differ from other non-empirical types of articles and from each other. Finally, we describe distinctions between conceptual and theory articles by clarifying their focus and goals and approaches to writing them. We illustrate these distinctions with examples of articles published in Human Resource Development Review . The article concludes with a discussion and implications for the field, the journal editors, and researchers.